Implementation of a YouTube channel to support a Physics course - Arguedas Matarrita, Carlos Alberto; Herrera Molina, Eric William (Atenas, 2016)
To provide support to Physics I for the teaching of a science course, several video tutorials were produced and grouped in a YouTube channel. This work was validated by a group of students from Physics II for the teaching of science course. This channel gives students the opportunity to analyze the resolution of problems related to the different topics of the course.